Оцінка ефективності попереджувальної діяльності прокуратури як суб'єкта запобігання та протидії злочинності у сучасний період - Супруненко, Д.; Suprunenko, D. (Східноєвропейський національний університет імені Лесі Українки, 2016)
В статі на підставі вивчення змісту нормативно-правових актів, що регулюють діяльність прокуратури України, а також аналізу результатів роботи по запобіганню злочинам в органах та установах виконання покарань, визначені проблемні питання та виведені науково обґрунтовані шляхи їх вирішення по суті. Сформульвано пропозицію щодо доповнення ст. 2 Закону України «Про прокуратуру» такою функцією прокуратури, як нагляд за дотриманням кримінологічного законодавства, спрямованого на усунення причин і умов, що сприяли вчиненню злочинів та інших правопорушень, виявлених у результаті реалізації інших функцій прокуратури. The article identifies problems and derives scientifically substantiated ways of solving them per se on the basis of the thorough study of the content of regulations governing the activities of the Prosecutor's Office in Ukraine, and also the analysis of the results of work aimed at preventing crime in the judicial bodies and penal institutions. The author states that the purpose of coordination of the activities performed by the law enforcement agencies in the fight against criminality is to improve their preventive activity by combining efforts. The main tasks concerning this activity are: 1) creation of a united front tocombat crime; 2) revitalization of the activities of the entities responsible for preventive work; 3) saving of costs, capabilities and resources provided to prevent crime; 4) ensuring the implementation of government programs in the fight against crime; 5) developing strategy and recommendations for crime prevention tactics; 6) study and generalization of practice of the coordinating activities; 7) elimination of duplication and concurrency in the activity of crime prevention entities. The author suggests to supplement Article 2 of the Law «On Prosecution» of Ukraine with such function of prosecutor's office as supervision over the compliance with criminological legislation, aimed at eliminating the causes and conditions that contributed to the commission of crime and other offenses, discovered in the results of realization of other functions of the prosecution.
Estimation of the Efficiency of Preventive Activities of Prosecution as an Institution for Prevention and Countering Crimes inthe Modern Period.
Keywords: запобігання злочинам; прокуратура; органи виконання покарань; установи виконання покарань; нормативно-правовий акт; прокурорський нагляд; суб’єкт запобігання злочинам; crime prevention; Prosecutor's Office; penal authorities; penal institutions; legal act; prosecutor’s supervision; subject of crime prevention